Effect of salat on blood pressure and pulse rate in stage one primary hypertension patients - Legiran Legiran; Ratika Febriani; Muhammad Ridho Mubarak; Sandra Pakpahan (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Hypertension is included in 15 major causes of death in the United States. Primary prevention and prompt treatment of hypertension can prevent mortality. Previous research on salat revealed that prayer provides a feeling of relaxation and activates parasympathetic activation, affecting the cardiovascular system. Objective: This study aims to investigate the effect of salat on blood pressure (BP) and pulse in patients with stage one primary hypertension.Methods: This is a quasi-experimental study with a non-equivalent pre- and post-test control group design. The sample was taken by purposive sampling method. Thirty-six outpatients with stage one primary hypertension who met the inclusion and exclusion criteria were included. The data were analysed by the Friedman and Wilcoxon post-hoc follow-up tests.Results: The statistical analysis showed significant differences in systolic BP (SBP) at 5 minutes after salat, 10 minutes after salat, and 5 minutes vs 10 minutes after salat, both in the treatment and control groups. For the diastolic BP (DBP), a significant difference was found at 5 minutes after salat and 10 minutes after salat in the treatment group, as well as at 10 minutes after salat and 5 minutes after salat vs 10 minutes after salat in the control group. For the pulse variable, a significant difference was found at 5 minutes after salat and 10 minutes after salat in the treatment group, and 5 minutes after salat in the control group.Conclusion: There is a decrease in BP and pulse rate in patients with stage one hypertension after salat.